Imunossensor reutilizável para a detecção de proteína c-reativa em soro humano - Ribeiro, Sandro Henrique Dias (2019)
C-reactive protein (CRP) is an important marker of inflammatory process and / or tissue injury and is associated with the development of cardiovascular diseases, especially in the formation of atherosclerotic plaque. Its serum levels are useful in monitoring inflammatory activity, in treatment and clinical evolution, and in detecting post-operative infectious complications. Thus, the quantification of CRP is of extreme clinical importance to aid in the diagnosis and minimization of disease worsening. Biosensors are potential alternatives to existing conventional diagnostic methodologies, especially for low cost, speed, accuracy, specificity and portability. This work describes the preparation of a reusable electrochemical immunosensor based in modified carbon electrode with reduced graphene oxide and polytyramine for the detection of C-reactive protein (CRP) in serum. This immunosensor was able to distinguish different concentrations of CRP in enriched serum and serum from human patients by differential pulse voltammetry, with a detection limit of 0.37 μg mL-1 and quantification limit of 1.25 μg mL-1. Analyses by atomic force microscopy, scanning electron miscroscopy and electrochemical impedance spectroscopy corroborated with voltammetric analysis. The immunosensor showed selectivity, regeneration capacity and stability, about 90% for 50 days of storage, also allowing the comparison of the CRP levels obtained with the laboratory data and, therefore, a promising platform for quantification of CRP in point-of- care.